Game Edukasi Anak Autis Guna Melatih dan Merehabilitasi Gerak Motorik Berbasis Kinect Bertema Anggota Keluarga - Rohmah, Arini Nur; , Fatah Yasin Al Irsyadi, S.T., M.T (2017)
Children with autism spectrum disorder or autism, require more intensive guidance to learn new subject. Besides having difficulty in focus, unpredictable and uncontrollable motoric movements are main factors which hinder their studies. Sometimes children with autism are unable to distinguish between multiple object. The aim of this research is to introduce family members and daily objects to children with autism by using game based on Kinect. This educational game is expected to be able to present primary family members which are father, mother, older brother, and little sister to autistic children in more pleasant way. This game can also be used to train focus ability and motoric movements of autistic children thus they can easily absorb the subject given in the game. This research is held in "Sekolah Rumah PintarAnak Berkebutuhan Khusus (ABK)", Salatiga and the subject used is based on the syllabus for elementary school of children with autism spectrum disorder. Autistic children get bored quickly when paying attention to a single repetitive stimulus for long periods of time or when facing the subject which is not interesting for them. Introducing family members in the different way like using animation with supported sound will make them more excited in learning the subject. This Kinect-base educational game was designed in reference to the results of interviews with the teacher and observations in Sekolah Rumah Pintar (ABK). The primary software used to built this game are Unity 2D/3D and Kinect SDK. The assets of the game were made using Inkscape software and the animations are made using DragonBones software. In a trial stage of this application, the students of Sekolah Rumah Pintar accompanied by their teachers are asked to play this game. From the questioner filled by the teachers of Sekolah Rumah Pintar (ABK), this game greatly attracts the attention of children with autism. This game is not only can help rehabilitating the motoric movements of children with autism but also can be used as a studying material for autistic children in elementary school.